2006
DOI: 10.1111/j.1472-765x.2006.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the methods for enumerating coliform bacteria from water samples using precise reference standards

Abstract: Aims:  To use BioBallTM cultures as a precise reference standard to evaluate methods for enumeration of Escherichia coli and other coliform bacteria in water samples. Methods and Results:  Eight methods were evaluated including membrane filtration, standard plate count (pour and spread plate methods), defined substrate technology methods (ColilertTM and ColisureTM), the most probable number method and the Petrifilm disposable plate method. Escherichia coli and Enterobacter aerogenes BioBallTM cultures containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…These figures agree with the work of Lebaron who in a much more extensive study using the discontinuous 4-MUG method for measuring GUS activity reported CVs less than 15% [25]. By comparison, culture based MPN methods typically report CVs of 15% to 30% [32]. …”
Section: Field Trialsupporting
confidence: 88%
“…These figures agree with the work of Lebaron who in a much more extensive study using the discontinuous 4-MUG method for measuring GUS activity reported CVs less than 15% [25]. By comparison, culture based MPN methods typically report CVs of 15% to 30% [32]. …”
Section: Field Trialsupporting
confidence: 88%
“…from time to time (6,10,21). Upon its isolation from blood (7 isolates) and stool samples (3 isolates) of 10 individuals within two days at the Clinical Microbiology laboratory, an outbreak investigation study was performed including molecular epidemiological studies by AP-PCR method.…”
Section: Discussionmentioning
confidence: 99%
“…Various human enteric pathogens, such as Salmonella spp., Cryptosporidium, Hepatitis A, Norwalk virus, and enteroviruses, have been found in surface waters (Lipp et al 2001;Griffin et al 2003;Wohlsen et al 2006;Ahmed et al 2009), and incidents of outbreaks are often recorded (Craun et al 2006;Arveloa et al 2012). However, it is not technically or economically feasible for water management agencies to screen for all waterborne pathogens.…”
Section: Introductionmentioning
confidence: 97%